2012
DOI: 10.1099/ijs.0.029058-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychrobacter sanguinis sp. nov., recovered from four clinical specimens over a 4-year period

Abstract: An analysis of 16S rRNA gene sequences from archived clinical reference specimens identified a novel species of the genus Psychrobacter, of which four strains have been independently isolated from human blood. On the basis of 16S rRNA gene sequence similarity, the closest relatives with validly published names were Psychrobacter arenosus R7 T (98.7 %), P. pulmonis CECT 5989 T (97.7 %), P. faecalis Iso-46 T (97.6 %) and P. lutiphocae IMMIB L-1110 T (97.2 %). Maximumlikelihood phylogenetic analysis of 16S rRNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…Whereas Psychrobacter spp. usually grow on marine agar, which contains 3.5% NaCl, our P. sanguinis isolate failed to grow on this specific medium, as described by Wirth et al (7). Moreover, our isolate was able to grow between the temperatures of 4°C and 37°C.…”
mentioning
confidence: 89%
“…Whereas Psychrobacter spp. usually grow on marine agar, which contains 3.5% NaCl, our P. sanguinis isolate failed to grow on this specific medium, as described by Wirth et al (7). Moreover, our isolate was able to grow between the temperatures of 4°C and 37°C.…”
mentioning
confidence: 89%
“…We report a first case in which P. sanguinis was isolated from human blood in Korea. In the six previously reported cases, we didn't detailed review for first reported case and the other three cases due to a lack of information in the literature [11] and two cases with meningitis were described as a probable infection [13] or a definite infection [12]. These cases were confirmed as a single organism with P. sanguinis infection by using molecular methods, and were treated with antibiotics.…”
Section: From 2004 To 2008 Human Blood Cultures Yielded Fourmentioning
confidence: 99%
“…This represented the first report of P. sanguinis in humans, and the type strain was isolated from the blood of an 84-year-old male in 2012 [11]. In 2014, P. sanguinis was isolated from the CSF of a 64-year-old female patient with post-neurosurgical meningitis, and this strain was identified only by 16S rRNA analysis [12].…”
Section: From 2004 To 2008 Human Blood Cultures Yielded Fourmentioning
confidence: 99%
See 2 more Smart Citations